The Effect of Cash Flow Volatility on Earnings Quality under Economic Uncertainty: Evidence from Indonesia - Dini Kamilia Salma; Muh Irshan Sachrir; Rafiqa Hastharita (Universitas Tidar, 2026)
This study examines the effect of cash flow volatility (CFV) on earnings quality (EQ), with the COVID-19 pandemic as a moderating variable. The sample comprises 3,127 firm-year observations of non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023, selected using purposive sampling and analyzed using panel data regression. The results indicate that higher CFV is associated with lower earnings quality. Although the COVID-19 pandemic is negatively associated with accrual estimation errors, the positive and significant interaction between CFV and the pandemic indicates that economic uncertainty intensifies the adverse effect of CFV on EQ. These findings highlight the importance of maintaining cash flow stability and strengthening financial reporting quality during periods of economic uncertainty.